Ödemiş-Dereuzunyer: Architectural Features of a Rural Settlement to Be Submerged by Dam Waters. Issue 4 (20th April 2020) - Kâhya, Yegan; Güler, Koray; Güler, Ayşe Ceren
ABSTRACT: The village of Dereuzunyer located in the Rahmanlar Valley of the Küçük Menderes Basin is a settlement that is a natural extension of a topography shaped by a joint contribution of culture and nature. It has preserved the authenticity and integrity of its traditional rural fabric and gives detailed information about the architectural approach, building technology, construction techniques, landscape features and traditional craftsmanship of past rural life. While some of the cultural assets in the settlement containing detailed information about the rural lifestyle of the past have survived to date despite the harsh natural conditions, the remainder have been neglected, become dilapidated, and fallen into ruin over time due to lack of maintenance by the local people because of rumors about the possible dam project and expropriations in progress. After completion of the Rahmanlar Dam in 2019, the cultural landscape values of Dereuzunyer will be lost irretrievably. This article aims to make a contribution to creating awareness about avoiding such losses, not only by introducing the non-renewable values of Dereuzunyer, by documentation of its historical development, its traditional architecture, its traditional building types, its construction techniques, and its plan and façade features, but also by promoting and interpreting its lost cultural heritage.